A new family of wurtzite-phase Cu2ZnAS4−x and CuZn2AS4 (A = Al, Ga, In) nanocrystals for solar energy conversion applications. Issue 2 (15th October 2015) - Ghosh, Anima; Palchoudhury, Soubantika; Thangavel, Rajalingam; Zhou, Ziyou; Naghibolashrafi, Nariman; Ramasamy, Karthik; Gupta, Arunava
Abstract : A new family of semiconductors Cu2 ZnAS4− x and CuZn2 AS4 (A = Al, Ga, In) that absorb strongly at visible wavelengths has been synthesized as nanocrystals. Abstract : A new family of quaternary semiconductors Cu2 ZnAS4− x and CuZn2 AS4 (A = Al, Ga, In) has been synthesized in the form of wurtzite phase nanocrystals for the first time. The nanocrystals can be converted to the stannite phase via thermal annealing under a N2 atmosphere. A direct band gap in the visible wavelength region combined with a high absorption cross-section makes these materials promising for solar energy conversion applications.